The media reality of preschool children in the opinion of children, teachers and parents - Eunika Baron-Polańczyk; Barbara Walas (Studia z Teorii Wychowania)
The article presents a fragment of diagnostic research of a mixed nature, establishing the media reality of preschool children. It seeks answers to the question about the media reality of preschoolers in the opinions of children, teachers and parents. The diagnostic survey method (questionnaire, interview, document analysis) and statistical methods (chi-square test of independence, ANOVA, Phi coefficient, Cramer's V) were used. The study examined 100 6-year-old children, 100 parents and 16 pre-school teachers. It was established that: 1) pre-school children: have unlimited access to the mobile applications; they use media tools in an uncontrolled way at home; in kindergarten, they learn the rational and correct use of new technologies while playing and learning; 2) parents and teachers assess children's media competency at an average level; parents see advantages and disadvantages in the media usage by children; 3) children can independently install games on a tablet or smartphone, often their parents install them themselves (usually these are games inappropriate for children’s age); 4) there are significant differences between the opinion of children and the observations of parents regarding the use of media tools; preschoolers claimed that they use tablets more often, and parents most often indicated that the children mainly watch TV; 5) calculations of differentiating factors showed significant statistical differences only in one case – between teachers' opinion on the children’s level of media competency and the teachers’ degree of professional advancement; the higher the degree of advancement, the lower the assessment of the competency level represented by six-year-olds.